2019
DOI: 10.18502/npt.v6i3.1257
|View full text |Cite
|
Sign up to set email alerts
|

An aging simulation game’s impact on the attitudes of nursing students

Abstract: Background & Aim: The aging of the population poses new challenges, among others, a greater concern with the teaching of geriatrics and gerontology, especially to future health professionals. The simulation game "Aging Nursing Game" ® was used with the objective of evaluating the impact of an aging simulation game on nursing students' attitudes towards the elderly. Methods & Materials: A pre-test and post-test type quasi-experimental study was performed, without control group. The research was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Of the 11 pre/post intervention without control studies in this review, eight reported a significant improvement in attitudes to older people, using a range of scales (Booth & Kada, 2015; Chen et al., 2015a, 2015b; de Abreu et al., 2017; Evans et al., 2005; Fernandes et al., 2019; Halpin, 2015; Varkey et al., 2006). One study (Robinson & Rosher, 2001) found no overall difference in attitude post intervention on the ASD, but did find a significant improvement on the instrumental subscale which related to attitudes to older people's ability to improve, change and pursue goals.…”
Section: Resultsmentioning
confidence: 98%
“…Of the 11 pre/post intervention without control studies in this review, eight reported a significant improvement in attitudes to older people, using a range of scales (Booth & Kada, 2015; Chen et al., 2015a, 2015b; de Abreu et al., 2017; Evans et al., 2005; Fernandes et al., 2019; Halpin, 2015; Varkey et al., 2006). One study (Robinson & Rosher, 2001) found no overall difference in attitude post intervention on the ASD, but did find a significant improvement on the instrumental subscale which related to attitudes to older people's ability to improve, change and pursue goals.…”
Section: Resultsmentioning
confidence: 98%
“…In this study, it was determined that nursing and medical students had positive attitudes to the older people. Various studies reported that both nursing (26,27,29,30) and medical students (31) had positive attitudes towards the older people, while some others reported negative attitudes (3,5,32). In our study, although the change in the mean scores of the students for the older people attitudes differs in relation with the colleges, the difference between the experimental and control group students also changes.…”
Section: Discussionmentioning
confidence: 99%
“…Any study investigating the effect of role playing on developing positive attitudes towards the older people is not available in the literature. However, there are studies related to the effects of the age simulation suit on the older people attitude, and some studies reported that the aged simulation suit was effective in developing positive attitudes (7,26,27) particularly in students, while some others suggested that it has a negative effect (18,33). Different interventions used in different studies may be reason for these diverse results.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, gamification has aroused considerable interest in various fields, including health [ 5 , 6 , 7 , 8 ]. Moreover, the diffusion of technological and computer tools has contributed to the use of new methodologies, strategies, and resources in teaching [ 2 , 5 ], specifically in the education of healthcare professionals [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strategic use of gamification in healthcare professions education aims to improve learning outcomes, promote behavioral changes, and enhance clinical skills through greater engagement and practice in a risk-free environment [ 6 , 7 ]. Within this context, exploring gamification in the teaching–learning process opens various innovative possibilities, among which we highlight the use of serious games.…”
Section: Introductionmentioning
confidence: 99%